SOME ASPECTS OF MINERALOGICAL CRYSTALLOGRAPHY IN THE WORKS OF V.I. VERNADSKY - Kvasnytsya, V.; Kvasnytsya, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Some aspects of mineralogical crystallography in the mineralogical and crystallographic works of V.I. Vernadsky are examined. In comparison with the material of these works new data on crystallomorphology of native elements, including diamond, gold and native copper are highlight. Peculiarities of crystallomorphology of native gold and copper from deposits and ore occurrences of Ukraine are established. New data on crystallomorphology of mantle and impact diamonds are discussed.